Hydroxytyrosol: biological activities and potential application in livestock production - Gao, Yang; Liu, Wenhui; Pan, Shengsheng; Li, Jiahui; Wang, Jingwei; Chen, Lin; Ma, Xue; Leng, Huan (Frontiers in Veterinary Science, 2025)
Hydroxytyrosol (HT) is a polyphenol compound that is widely present in the leaves and fruits of olive in the form of esters, which is one of the natural antioxidants. In recent years, a large number of studies have found that HT has good activity in anti-oxidant, anti-inflammatory, lipids lowering and other physiological functions. The purpose of this article is to provide solutions for the development of new feed additives under the premise of a complete ban on the use of antibiotics. In this review, we concluded the reports on HT in recent years and summarized its source, synthesis, digestion, absorption and metabolism of HT, as well as its main physiological functions, application prospects in animal production. Therefore, HT can be used as a potential new feed additive so as to provide theoretical basis and guidance for the development and application of hydroxytyrosol in animal husbandry.